Rocuronium-Induced Dilated Nonreactive Pupils in a Patient With Coronavirus Disease 2019: A Case Report. Issue 7 (July 2021) - Rodrigues, Elba da Paixão; da Costa, Gustavo Caniné; Braga, Douglas Quintanilha; Pinto, Jorge Eduardo da Silva Soares; Lessa, Marcos Adriano
Abstract : We report the clinical case of a patient with coronavirus disease 2019 (COVID-19) who had recently undergone neurosurgery and presented with dilated nonreactive pupils during continuous rocuronium infusion, which was reversible with the suspension of the drug. Both the neurosurgical procedure and possible disruption of the blood–brain barrier due to COVID-19 infection may have led to the action of rocuronium in the central nervous system (CNS). Thus, clinicians must remember that neuromuscular blocking agents (NMBAs) can cause dilated nonreactive pupils in patients with COVID-19.